2020
DOI: 10.1021/acsami.0c09357
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Periodic Bowtie SERS Substrate with Narrow Nanogaps Obtained by Monitored Pulsed Electrodeposition

Abstract: Surface-enhanced Raman spectroscopy (SERS) is a highly sensitive technique with molecular specificity, making it an ideal analytical tool in various fields. However, the breadth of practical applications of SERS has been severely limited because it is still a great challenge to achieve simultaneously a high sensitivity and a high reproducibility. Herein, we report a highly controllable method to fabricate periodic bowtie SERS substrates with a narrow nanogap, high SERS enhancement, and good uniformity over a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…SERS‐based bioanalytical applications involve the interactions of SERS substrate with complex biological systems. [ 14‐16 ] Undoubtedly, the SERS substrate is a pivotal factor for governing sensitivity and reproducibility of SERS bioanalysis. [ 17‐19 ] Au nanocrystals (Au NCs) with strong surface plasmonic resonance (SPR) properties and superior chemical stability have been extensively used as SERS substrates.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…SERS‐based bioanalytical applications involve the interactions of SERS substrate with complex biological systems. [ 14‐16 ] Undoubtedly, the SERS substrate is a pivotal factor for governing sensitivity and reproducibility of SERS bioanalysis. [ 17‐19 ] Au nanocrystals (Au NCs) with strong surface plasmonic resonance (SPR) properties and superior chemical stability have been extensively used as SERS substrates.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 63 ] Raman enhancement factors as high as 10 9 for metal nanogaps have been observed experimentally and this is sufficient for use in the detection of single molecules. [ 64,65 ] Several approaches to the manufacture of nanogaps with controllable spacing have been proposed, including electron‐beam lithography, [ 66 ] the mechanical break junction method, [ 67 ] electromigration, [ 68 ] electrochemical deposition, [ 69 ] and atomic layer deposition. [ 70 ] However, the characteristics of these serial methods are unsuitable for high‐throughput and low‐cost manufacturing applications.…”
Section: Application Development Of Nanoskivingmentioning
confidence: 99%
“…Cells can be seeded on SERS substrates, and once they adhered and spread, their chemical composition near the surface can be studied by irradiating the substrate and measuring the Raman spectra. Over the years, a wide diversity of metal nanostructured surfaces have been created for SERS, such as nanoparticles attached to a surface (Freeman et al, 1995;Zhai et al, 2009;Lussier et al, 2016), nanopillars (Kang et al, 2015;Li et al, 2016), nanoholes (Abdelsalam et al, 2005;Luo et al, 2019), and others (Yüksel et al, 2017;Yao et al, 2020). A detailed review on the fabrication of SERS substrates can be found in Fan et al (2011).…”
Section: Cell Adhesion Biomarkersmentioning
confidence: 99%